2010
DOI: 10.1111/j.1601-0825.2009.01608.x
|View full text |Cite
|
Sign up to set email alerts
|

FOXP3+ T regulatory cells in lesions of oral lichen planus correlated with disease activity

Abstract: OBJECTIVE: The aim of this study was to determine the correlation between the number of FOXP3 + T cell in lesions and the disease activity of patients with oral lichen planus (OLP). MATERIALS AND METHODS: The expression of FOXP3 was investigated using immunohistochemical staining and real-time RT-PCR in 23 OLP lesions and 12 controls. Changes of FOXP3 + Treg in peripheral blood from three patients' pre and post-treatment were assessed using flow cytometry. RESULTS: Few FOXP3 + cells were detected in controls, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 34 publications
5
43
0
3
Order By: Relevance
“…cells in OLP than in the NSI group and that they were situated in the superficial connective tissue, subjacent the epithelium corroborating the results of others [16,18,20]. Double IF demonstrated that the FoxP3 ?…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…cells in OLP than in the NSI group and that they were situated in the superficial connective tissue, subjacent the epithelium corroborating the results of others [16,18,20]. Double IF demonstrated that the FoxP3 ?…”
Section: Discussionsupporting
confidence: 91%
“…cells were CD3 ? T cells, reflecting the findings of Tao (2010) [20]. Tregs are involved in immunoregulation, particularly control of autoimmunity through cell-cell contact-mediated suppression.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Treg and TAM cells are key components of the tumor microenvironment, but Foxp3 is not expressed in normal oral mucosa [20]. In keeping with that observation, we found that OLP, OLK, and OSCC tissues contained inflammatory regions that were infiltrated to different extents by CD4 + T-cells and CD68 + macrophages and that OSCC tissues contained more CD4 + T-cells and CD68 + macrophages than either OLP or OLK tissue.…”
Section: Discussionsupporting
confidence: 85%
“…21 Yet in another study, which calculated the IFN-γ/IL-4 ratio in lesional tissue and unstimulated whole saliva, the expression of both cytokines were elevated and the IFN-γ/IL-4 ratio showed no significant difference in OLP patients and healthy controls. These controversies might partly be caused by the difference of patients, research methods or sample sizes, but it also implied that there might be some mechanisms, such as the role of regulatory T cells 22 and new subsets of Th cells, 23 in the etiology of OLP other than Th1/Th2 imbalance.…”
Section: Discussionmentioning
confidence: 99%